A Highly Fluorescent and Photoresponsive Polymer Gel Consisting of Poly(acrylic acid) and Supramolecular Cyanostilbene Crosslinkers. Issue 4 (14th December 2018) - Kim, Hyeong‐Ju; Lee, Hyun Jun; Chung, Jong Won; Whang, Dong Ryeol; Park, Soo Young
Abstract: A poly(acrylic acid)‐based polymer gel exhibiting strong fluorescence and high photoresponsibility is prepared by using a cyanostilbene derivative as a self‐assembling supramolecular crosslinking agent, which generates conceptually new multiple hydrogen bonds in the gel system. This polymer gel in ethanol shows the gel‐to‐sol transition upon UV light irradiation with concomitant fluorescence color and intensity changes, which are attributed to the trans ‐to‐ cis photoisomerization of the supramolecular crosslinkers. Aggregation‐induced enhanced emission (AIEE) behavior of the trans ‐cyanostilbene derivative enables a highly fluorescent polymer gel (ΦF = 0.68) with green color (λem = 541 nm), which can be switched into a blue fluorescent sol (λem = 506 nm and ΦF = 0.12) upon UV irradiation. Abstract : On the basis of new conceptual self‐assembling supramolecular crosslinkers creating the crosslinking power of multiple hydrogen bonds, a highly luminescent and efficiently photoresponsive polymer gel system is successfully materialized. This self‐assembling supramolecular crosslinker‐based polymer gel shows effective gel‐to‐sol transition upon UV light irradiation with concomitant fluorescence change, which is triggered by the trans ‐to‐ cis photoisomerization of the supramolecular crosslinkers.